Promoting Equitable Biology Lab Instruction by Engaging All Students in a Broad Range of Science Practices: An Exploratory Study. (March 2017) - Strimaitis, Anna M.; Southerland, Sherry A.; Sampson, Victor; Enderle, Patrick; Grooms, Jonathon
Abstract : This study examines what students enrolled in the honors and general sections of a high school biology course offered at the same school learn when they have an opportunity to participate in a broad or narrow range of science practices during their laboratory experiences. The results of our analysis suggest that the students enrolled in the general sections of the course made similar or larger gains than the students enrolled in the honors section of the course in their abilities to plan and carry out an investigation, argue from evidence, and write a science‐specific persuasive essay when these students had an opportunity to participate in a broad range of science practices. These findings suggest that laboratory experiences that give students an opportunity to participate in a broad range of science practices, although considered challenging by many teachers, have the potential to help all students become more proficient in science. The article concludes with a discussion of the implications of this study for classroom instruction and educational policy.